Techniques to Identify and Test PCB Faults with Proposed Solution - Ambreen Insaf,; Mirza Salman Baig,; Zeeshan Alam Nayyar ,; Mirza Aman Baig, (Journal of Basic & Applied Sciences, 2014)
Printed Circuit Boards (PCBs) are getting more complex day by day because of vast and modern technology. Analyzing PCB’s failure and their reason of failing is a challenging task but despite how faulty they may be, they can be diagnosed and repair. Modern PCBs consist of fine pitch components including unidentified, non-testable and customized parts, which make it difficult to troubleshoot and repair. Modern PCBs cannot test and repair using generic Automatic Test Equipments (ATEs), unlike simple ones. Successful repair of such types of PCBs is an art more than science. PCB troubleshooting and fault analysis needs a good theoretical knowledge and analytical thinking. It is not something, which can only study from books, but it can gain through constant troubleshooting and experiencing. Keeping in view above mentioned problems this research focused on exploring diagnosis skills and techniques used to identify faults in such Integrated Circuits (ICs) and components using VI instrument. As a result, reducing equipment downtime and high costs need in PCB repairs.